Misc Simplify this expression: 4p + 9 + (-7p) + 2 by soetrust December 24, 2021 Leave a reply 8 THIS USER ASKED ๐ Simplify this expression: 4p + 9 + (-7p) + 2 THIS IS THE BEST ANSWER ๐ 4p + 9 + (-7p) + 2 = 4p + 9 – 7p + 2 = -3p +11 FacebookTwitterPinterestLinkedinEmail Related Posts:15. Simplify this expression: 13 + (โ12) โ (โ5) = ?…Simplify the following expression: 35 + (โ13) + (+8) โ (โ6).Simplify:mc001-1.jpgSimplify 4 + (-3) - 2 ร (-6) A. 13 B. -11 C. 12 D. -10Simplify (3a4 โ 2a2 + 5a โ 10) โ (2a4 + 4a2 + 5a โ…Simplify 12 โ (โ8) ร 4 = ?